Synthesis, molecular docking and comparative efficacy of various alkyl/aryl thioureas as antibacterial, antifungal and α-amylase inhibitors. (December 2018) - Larik, Fayaz Ali; Saeed, Aamer; Faisal, Muahmmad; Channar, Pervaiz Ali; Azam, Syed Sikandar; Ismail, Hammad; Dilshad, Erum; Mirza, Bushra
Graphical abstract: Highlights: A small library of 1-alkyl/acyl-3-(2-cyano-4-nitrophenyl) thiourea was synthesized in good yields. The newly synthesized compounds were evaluated for various biological studies. The compound 4e and 4b were found to be most potent inhibitors of α-amylase having IC50 9.7 μg/ml and 9.1 μg/ml. Molecular docking studies were carried out to find out the binding mode of the inhibitors with the enzyme. Abstract: Thioureas are exquisite building blocks for the construction of five and six membered heterocyclic units, and also display an extensive range of biological activities. 4-Nitro-2-cyano aniline was reacted with the various acid chlorides which were freshly prepared from carboxylic acids to afford the desired products in good yield. All the newly synthesized compounds were evaluated antibacterial, antifungal, antioxidant and α-amylase activity. The compounds showed significant activity against bacteria and fungi. The compound 4e and 4b were found to be most inhibitors of α-amylase having IC50 9.7 μg/ml and 9.1 μg/ml. Further molecular docking studies were carried out to find out the binding mode of the inhibitors with the enzyme.